ANALISIS KINERJA RUAS JALAN ANGKATAN 66 AKIBAT PEMBANGUNAN FLYOVER SIMPANG ANGKATAN 66 KOTA PALEMBANG - Dwi Fauzan, Muhammad; Firdaus, Firdaus (Lembaga Penelitian dan Penerbitan Hasil Penelitian Ensiklopedia, 2024)
Roads are a means of transportation that have two main functions, namely: increasing traffic capacity and providing connecting routes to the surrounding land. Population growth encourages an increase in the number of motorized vehicle owners which will affect traffic volume and road performance.This research aims to determine the level of service on The Angkatan 66 road. The analysis was carried out using primary data and secondary data. The Angkatan 66 road section is a 2-way, 2-lane undivided road with a road length of 0.9 km and a road width of 6 meters. The traffic volume survey was carried out for 7 days with the aim of finding out peak/busy hours, and the survey was carried out at 07:00 – 09:00 WIB, 11:00 – 13:00 WIB and 16:00 – 18:00 WIB . Road performance analysis refers to the 2014 Indonesian Road Capacity Guidelines (PKJI) with the degree of saturation (Dj) as the main indicator of road performance. Based on the LHR survey, it was found that the peak hour of traffic flow from The Angkatan 66 road at Point 1 on Monday 8 January 2024 at 08.00 – 09.00 was 2053 vehicles/hour with analysis results of 1195 cur/hour. From the calculation results, the capacity is 2170 cur/hour, the highest degree of saturation (Dj) is 0.55 and the travel speed is 39-51 km/hour and the service level is D.Keywords: Road, Traffic, Road Service Level.